Intraoral Applications of Lasers in the Prosthetic Rehabilitation with Fixed Partial Dentures-A Narrative Review - Magdalena Kwaśna; Paulina Cłapińska; Zuzanna Piosik; Kamila Barysz; Iga Dubiec; Adam Bęben; Iwona Ordyniec-Kwaśnica (MDPI AG, 2024)
Laser, an acronym for Light Amplification by Stimulated Emission of Radiation, is a powerful tool with diverse applications in modern dentistry. It emits monochromatic, coherent light resulting from photon-induced chain reactions. Available dental lasers include diode, argon, Er,Cr:YSGG, Er:YAG, Nd:YAG, and CO2. The unique property of these lasers, allowing them to be effectively used on both soft and hard tissues based on the operational parameters, positions them as particularly suited for a wide range of dental procedures. Compared to traditional methods, lasers offer advantages such as improved hemostasis and quicker wound healing. Such benefits stress the shift towards laser technology in dental treatment. In the realm of dental prosthodontics, which focuses on esthetics, functionality, and the physiological aspects of dental prostheses, lasers provide promising outcomes. Among the prosthetic options, fixed partial dentures stand out for their ability to mimic natural teeth, offering both esthetic and functional features, leading to satisfactory long-term outcomes if managed properly. This review paper delves into the specific application of laser technology in the context of prosthetic rehabilitation involving fixed partial dentures. By investigating intraoral laser procedures, it contributes to understanding laser's role in improving patients' satisfaction and clinical efficiency in this field.